2011
DOI: 10.3945/jn.111.139147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Organic Component of Low-Molecular-Weight Chromium-Binding Substance and Its Binding of Chromium

Abstract: Chromium was proposed to be an essential element over 50 y ago and was shown to have therapeutic potential in treating the symptoms of type 2 diabetes; however, its mechanism of action at a molecular level is unknown. One chromium-binding biomolecule, low-molecular weight chromium-binding substance (LMWCr or chromodulin), has been found to be biologically active in in vitro assays and proposed as a potential candidate for the in vivo biologically active form of chromium. Characterization of the organic compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…EEEEGDD is a fragment of low-molecular weight chromium-binding substance (LMWCr, also known as chromodulin), a biological peptide found in humans and animals that is involved in metabolism [6365] and may have utility in diabetes treatment [66]. We have recently sequenced a biological form of this peptide, pEEEEGDD [67]. This was a challenge because the high acidity of the peptide resulted in only deprotonation by ESI and MALDI.…”
Section: Resultsmentioning
confidence: 99%
“…EEEEGDD is a fragment of low-molecular weight chromium-binding substance (LMWCr, also known as chromodulin), a biological peptide found in humans and animals that is involved in metabolism [6365] and may have utility in diabetes treatment [66]. We have recently sequenced a biological form of this peptide, pEEEEGDD [67]. This was a challenge because the high acidity of the peptide resulted in only deprotonation by ESI and MALDI.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that trivalent chromium, Cr(III), readily cationizes acidic and neutral peptides [58, 68, 69] and that during CID these Cr(III)-peptide ions undergo extensive sequence-informative fragmentation [68]. Also, Cr(III) readily binds to acidic peptides in solution [10, 70, 71]. However, Cr(III) proved to be a poor choice for sequencing fibrinopeptide B by ETD (see Supplementary Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…This led to a number of studies designed to isolate and characterize endogenous LMWCr and synthetic molecular mimics of LMWCr . A recently published report claims to have characterized the structure of the apoLMWCr which may pave way for future studies in understanding the role of the polypeptide in the management of diabetes [36]. …”
Section: Chromium and Insulin Signalingmentioning
confidence: 99%